Meta- Evaluation of Instruction of Classroom in University - Li, Kai; Sun, Hongchun (IJRDO- Journal of Educational Research, 2018)
Teaching evaluation is an important part of teaching work and an important means of scientific management in the field of teaching. Reasonable implementation of teaching evaluation activities is an effective guarantee for improving teaching quality. The meta- evaluation of teaching is to evaluate and study the quality and conclusion of teaching evaluation technology according to certain theoretical and value criteria. The meta-evaluation of teaching evaluation is to standardize the research of teaching evaluation, monitor the teaching evaluation activities, reduce the deviation, smoothly realize the evaluation purpose, better play the function of teaching evaluation, and obtain good evaluation benefits.